2019
DOI: 10.1016/j.pcd.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between number of contacts between previous dropouts with type 2 diabetes and health care professionals on glycaemic control: A cohort study in public primary health care

Abstract: Please cite this article in press as: T. Kauppila, et al., Relationship between number of contacts between previous dropouts with type 2 diabetes and health care professionals on glycaemic control: A cohort study in public primary health care, Prim. Care Diab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…To support this, a Danish study showed that systematic approach in planned follow-up contacts increased the level of well-controlled asthma by 20% and reduced uncontrolled asthma by 14% 29 . Advantages of more frequent contacts were also reported recently with type 2 diabetes patients who had stopped to attend to follow-up in diabetes clinics as prescribed: with more frequent contacts, they succeeded to improve their glycaemic control in primary diabetes health care 30 . Previous results support the assumption that with regular followup it is possible to improve control of a persistent disease.…”
Section: Discussionmentioning
confidence: 75%
“…To support this, a Danish study showed that systematic approach in planned follow-up contacts increased the level of well-controlled asthma by 20% and reduced uncontrolled asthma by 14% 29 . Advantages of more frequent contacts were also reported recently with type 2 diabetes patients who had stopped to attend to follow-up in diabetes clinics as prescribed: with more frequent contacts, they succeeded to improve their glycaemic control in primary diabetes health care 30 . Previous results support the assumption that with regular followup it is possible to improve control of a persistent disease.…”
Section: Discussionmentioning
confidence: 75%
“…Metformin has been shown to improve the prognosis of T2D patients [ 16 ]. The increasing communication, and thereby increasing exchange of information, between the T2D treatment system and the recruited “LTFs” with improved glycaemic control which we observed [ 6 ] did not solely explain the improved glycaemic status. Recommendation based [ 13 15 ] increases in medication also seemed to be required for favourable results in T2D treatment of the “LTFs”.…”
Section: Discussionmentioning
confidence: 70%
“…One group was defined as "LTFs" with an improvement in glycaemic control, e.g. those who had a HbA 1 c level ≥53 mmol/mol (7%) at the baseline visit and a reduction in HbA 1 c ≥ 6 mmol/mol (0.5%) at the follow-up visit 12-30 months later [6]. The second group was defined as "LTFs" without improvement, e.g.…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations